PENGEMBANGAN ATMOSFER KEWIRAUSAHAAN MELALUI EKONOMI KREATIF BERBASIS TEKNOLOGI INFORMASI DI IIB DARMAJAYA [THE DEVELOPMENT OF ENTREPRENEURSHIP ATMOSPHERE THROUGH CREATIVE ECONOMY BASED ON INFORMATION TECHNOLOGY ON IIB DARMAJAYA] - Muhamad Ariza Eka Yusendra; Niken Paramitasari; Dedi Putra; Ketut Artaye (Jurnal Sinergitas PKM & CSR, 2018)
The community service activities carried out by community service teams of IIB Darmajaya is part of the scheme of Entrepreneurship Development Program from Kemenristekdikti grant. The focus of Entrepreneurship Development Program are the implementation of the campus entrepreneurial atmosphere development model through the integration of various functions at the Campus of IIB Darmajaya, starting from strengthening busines and technology incubator, colaboration of various campus internal department, establishing an academic system which supports entrepreneurial learning, introducing information technological based creative economy to students as the foundation for their business and the involvement of entreprenuerial community. The community service methods were carried out are seminars, lectures, training and workshop, consultation to coordination with stakeholder which have important role in determining the success of tenants on developing their business. The results of this community service activities are an integrative campus entrepreneurship development process and 8 tenants students who will be nurtured by business and technology incubator of IIB Darmajaya with also involving entrepreneur lecturers. Its hoped with the success of this Entrepreneurship Development Program, it will become an example for other universities that want to develop an information technological based creative economy atmosphere effectively.